2022
DOI: 10.3389/fphar.2022.899798
|View full text |Cite
|
Sign up to set email alerts
|

How to Achieve Sufficient Endogenous Insulin Suppression in Euglycemic Clamps Assessing the Pharmacokinetics and Pharmacodynamics of Long-Acting Insulin Preparations Employing Healthy Volunteers

Abstract: The therapeutic effect of basal insulin analogs will be sustained at a rather low insulin level. When employing healthy volunteers to assess the pharmacokinetics (PK) and pharmacodynamics (PD) of long-acting insulin preparations by euglycemic clamp techniques, endogenous insulin cannot be ignored and sufficient endogenous insulin inhibition is crucial for the PD and/or PK assessment. This study aimed to explore a way to sufficiently inhibit endogenous insulin secretion. Healthy Chinese male and female voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…20,21 Cpeptide has a long half-life and can re ect the secretion of endogenous insulin; therefore, it is frequently used to evaluate the index of endogenous insulin. Previous studies 22,23 have indicated that endogenous insulin inhibition is su cient if the C-peptide inhibition rate is > 50%. Therefore, we categorized the participants into two groups according to the C-peptide reduction ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 Cpeptide has a long half-life and can re ect the secretion of endogenous insulin; therefore, it is frequently used to evaluate the index of endogenous insulin. Previous studies 22,23 have indicated that endogenous insulin inhibition is su cient if the C-peptide inhibition rate is > 50%. Therefore, we categorized the participants into two groups according to the C-peptide reduction ratio.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reduction in the ratio of C-peptide in Group D (C-peptide reduction ≥ 50%) was signi cantly higher than that in Group C (C-peptide reduction < 50%), which is consistent with previous studies. [22][23][24] The process of the euglycemic clamp test is affected by various factors, such as the basal metabolic state of volunteers, basal glucose and insulin levels before injection of exogenous insulin, the dosage of insulin preparations, insulin sensitivity, and BG regulation during the euglycemic clamp test. 20,25 In this study, we screened healthy volunteers strictly according to the prede ned inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to identify variations of endogenous insulin secretion during the clamp procedure. 18 C-peptide-based correction methods were employed for primary analyses of PK and PD parameters to further rule out any impact of endogenous insulin on the PK or PD outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…C‐peptide levels were determined, in parallel, to identify subjects whose endogenous insulin production may potentially interfere with insulin PK and PD measurements, i.e. to identify variations of endogenous insulin secretion during the clamp procedure 18 . C‐peptide‐based correction methods were employed for primary analyses of PK and PD parameters to further rule out any impact of endogenous insulin on the PK or PD outcomes.…”
Section: Methodsmentioning
confidence: 99%